Diaphragm, method of manufacture and use

CN123018354APending Publication Date: 2026-10-30HUNAN CHINALY NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611281072.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

针对现有半固态锂离子电池隔膜的离子电导率欠佳的问题,本发明的第一目的在于提供一种隔膜;

Benefits of technology

针对技术中存在的问题:在半固态体系中,离子必须在固态电解质颗粒之间,以及固态电解质与电极活性颗粒之间传输,固-固接触是点对点的刚性接触,有效接触面积小,且在界面处极易因晶格失配、杂质等原因形成高阻抗的“界面阻挡层”,导致半固态电池的宏观表观离子电导率远低于电解质材料自身的本征值的问题:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018354A_ABST
    Figure CN123018354A_ABST
Patent Text Reader

Abstract

The application discloses a diaphragm, a preparation method and application, and relates to the technical field of diaphragms. The application introduces a solid-state electrolyte forming a solid solution phase into the diaphragm, increases an effective contact area, reduces lattice mismatch and impurities, and effectively improves ion conductivity. In addition, electrode materials do not obviously swell and shrink in volume during the charging and discharging process, and can effectively enhance the mechanical strength and structural stability of the diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of diaphragm technology, and more specifically, relates to a diaphragm, its preparation method, and its application. Background Technology

[0002] Lithium-ion batteries offer advantages such as high energy density, long cycle life, low self-discharge rate, and no memory effect, storing more electrical energy than other technologies within the same weight or volume. Existing lithium-ion batteries are categorized by electrolyte type into liquid lithium-ion batteries, solid-state lithium-ion batteries, and semi-solid-state lithium-ion batteries. Liquid lithium-ion batteries use flammable organic liquids as electrolytes, posing a high risk of thermal runaway and ignition / explosion, with a theoretical energy density of 300-350 Wh / kg. Solid-state electrolytes replace organic liquid electrolytes, offering advantages such as non-flammability, non-volatility, and no leakage risk, but their technological barriers are high. Semi-solid-state batteries combine some of the maturity of liquid lithium-ion batteries with some of the forward-looking advantages of solid-state batteries, but their ionic conductivity is relatively low.

[0003] In existing technologies, solid electrolyte particles are added to the separator of semi-solid lithium-ion batteries. However, the lithium-ion migration rate of most solid electrolytes is still much lower than that of mature liquid electrolytes. The solids are in rigid contact with each other and cannot wet and fill all the pores of the electrode material like a liquid. This results in slow charging and discharging, low power, and poor conductivity of semi-solid lithium-ion batteries.

[0004] Therefore, improving the ionic conductivity of semi-solid lithium-ion battery separators is particularly important, as it affects the ionic conductivity of lithium-ion batteries. Summary of the Invention

[0005] 1. The problem to be solved To address the problem of poor ionic conductivity in existing semi-solid lithium-ion battery separators, the primary objective of this invention is to provide a separator. A second objective of this invention is to provide a method for preparing the aforementioned diaphragm; A third objective of the present invention is to provide a lithium-ion battery comprising the above-described separator.

[0006] 2. Technical Solution To solve the above problems, the technical solution adopted by the present invention is as follows: The first aspect of this invention discloses a diaphragm, comprising: Base membrane: Polyolefin separator; Coating layer: coated on one or both sides of the base film, the coating layer includes a solid electrolyte material, the solid electrolyte material is a solid solution formed by LATP and LAGP, and is prepared by Hf and / or Zr doping, wherein the mass ratio of LATP to LAGP is (4:1) to (1:4).

[0007] According to any embodiment of the first aspect of the present invention, the solid electrolyte material is Li a Al b M1 x M2 y M3 m M4 n (PO4) c , Where M1 is Zr, M2 is Hf, M3 is Ti, M4 is Ge, a=1.4~1.6, b=0.4~0.6, c=3, x=0~0.1, y=0~0.1, m=0.1~1.5, n=0.1~1.5, and x and y are not both 0.

[0008] The solid electrolyte material mentioned herein is LATP (Li 1.4 Al 0.4 Ti 1.6 (PO4)3, lithium aluminum titanium phosphate) and LAGP (Li 1.5 Al 0.5 Ge 1.5 The solid solution formed by (PO4)3 (lithium aluminum germanium phosphate) is more effective than a single LATP or LAGP, or a physical mixture of LATP and LAGP. Sintering two types of LATP and LAGP together to form a solid solution is beneficial for improving the overall mechanical strength of the crystal lattice, effectively suppressing lithium dendrite penetration, stabilizing the electrolyte-lithium metal interface, and minimizing the increase in interface impedance over long-term cycling. It also improves the ionic conductivity of the separator, significantly enhancing the cycle stability and safety of lithium metal batteries.

[0009] The solid solution is doped with Zr and / or Hf, where Zr is generally present in the form of Zr in the solid solution. 4+ Hf exists in solid solutions, generally as Hf 4+ The form exists, and the role of doping with Zr is to prevent Ti from being present. 4+ Oxidation simultaneously broadens lithium-ion migration channels and improves the room-temperature ionic conductivity of the material; doping with Hf enhances the stability of the crystal framework, further hindering the oxidation of Ti. 4+ Reduction side reactions occur, which simultaneously improve the electrochemical stability of the material and broaden the electrochemical window.

[0010] Among them, the amount of Zr doping is too high, that is, Zr 4+ Excessive Zr doping exacerbates lattice distortion, easily leading to the formation of zirconate impurities, coarse grains, increased grain boundary impedance, decreased ionic conductivity, and poor sintering density. It also prevents the release of internal lattice stress, resulting in numerous microcracks within the ceramic. Lithium dendrites can penetrate along these cracks, posing a short-circuit risk to the battery. Insufficient Zr doping, i.e., insufficient Zr... 4+ If there is too little, the lattice stabilization effect will be insufficient, making it difficult to effectively confine Ti.4+ negative electrode side Ti 4+ It is easily reduced by metallic lithium, resulting in increased interfacial impedance and accelerated capacity decay during cycling.

[0011] The amount of Hf doped is too high, that is, Hf 4+ Excessive Hf doping leads to severe lattice distortion due to ion accumulation, resulting in impurity phases, narrowing of lithium-ion migration channels, and a significant decrease in conductivity; insufficient Hf doping... 4+ Too little, then for Ti 4+ The lattice binding ability of LATP is insufficient, resulting in a poorer reduction inhibition effect and an exacerbation of the side reactions at the LATP-lithium interface.

[0012] When Zr and Hf are incorporated simultaneously, they work synergistically, specifically Zr... 4+ Focusing on enhancing ion conductivity, Hf 4+ Both emphasize stable crystal structures and are tetravalently substituted Ti. 4+ It can suppress Ti to the greatest extent 4+ Reduction, balancing electrical conductivity and interface stability, is superior to single Zr / Hf doping. 4+ Doping energy slightly increases Ti 4+ Reduction potential, local region Ti during cycling 4+ It is still easily reduced to Ti by metallic lithium. 3+ This causes localized lattice collapse and rapid capacity decay during battery cycles. Hf 4+ With larger atomic weight and ionic radius, Hf doping can excessively broaden the local lattice and distort lithium-ion migration channels, while Li + The significant increase in activation energy during transitions is a drawback of Zr. Dual doping can significantly improve a series of shortcomings caused by single doping. 4+ Hf 4+ Uniformly dissolved within the LATP / LAGP lattice, it optimizes lithium-ion conduction efficiency and improves conductivity, while also stabilizing the Ti crystal structure. 4+ It improves the stability of the negative electrode interface, and its overall performance is significantly better than that of single-phase raw materials and simple physical mixtures.

[0013] According to any embodiment of the first aspect of the present invention, the diaphragm has b=0.4~0.5, m=0.2~1.3, and n=0.2~1.3.

[0014] According to any embodiment of the first aspect of the present invention, in the solid electrolyte material, the mass ratio of LATP to LAGP is (4:1) to (1:4); for example, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, preferably 4:1.

[0015] According to any embodiment of the first aspect of the invention, the average particle size D of the solid electrolyte material is...50 The thickness ranges from 0.70 μm to 1.4 μm, with a preferred thickness of 0.762 μm to 1.346 μm.

[0016] According to any embodiment of the first aspect of the invention, the molar ratio of Zr to Hf in the diaphragm is 0:1, 1:0, 3:2, 2:3, 1:1, preferably 1:1.

[0017] If the doping ratio of Zr and Hf is too high, Ti will experience problems during high-temperature cycling. 4+ Increased reduction level is beneficial to improving the ionic conductivity of the coated lithium-ion battery separator, but it reduces the overall lattice resistance to reduction. If the doping ratio of Zr and Hf is too small, the lithium-ion conduction resistance will increase, the room temperature ionic conductivity will decrease, and the rate performance will deteriorate.

[0018] According to any embodiment of the first aspect of the present invention, the polyolefin separator may be a polyethylene separator, a polypropylene separator, or a polyethylene-polypropylene copolymer separator.

[0019] According to any embodiment of the first aspect of the present invention, the method for preparing the solid electrolyte material includes the steps of: S1. Mix LATP and LAGP and sinter in air to form a solid solution; S2. The dopant source and the ground solid solution are calcined to form a metal-doped solid electrolyte material, thereby achieving atomic-level uniform dispersion of the dopant source.

[0020] According to any embodiment of the first aspect of the invention, the mass ratio of LATP to LAGP in the diaphragm is (4:1) to (1:4), for example 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, preferably 4:1.

[0021] According to any embodiment of the first aspect of the invention, in step S2, the doping source includes a first doping source.

[0022] The first doping source is used to provide the first doping element Zr. The first doping source is selected from at least one of ZrO(NO3)2·2H2O, Zr(NO3)4, ZrOCl2·8H2O, ZrO2, and Zr(CO3)2. The amount of the first doping element added satisfies the molar ratio of the first doping element to lithium in the solid solution as (0.04-0.1):(1.4~1.5), for example, 0.04:1.5, 0.05:1.5, 0.06:1.5, 0.07:1.5, 0.08:1.5, 0.09:1.5, 1.0:1.5, 0.04:1.4, 0.05:1.4, 0.06:1.4, 0.07:1.4, 0.08:1.4, 0.09:1.4, 1.0:1.4. According to any embodiment of the first aspect of the invention, in step S2, the doping source includes a second doping source.

[0023] The second doping source is used to provide the second doping element Hf. The second doping source is selected from at least one of HfO(NO3)2·2H2O, HfCl4, HfO2, and Hf(OH)4. The amount of the second doping element added satisfies the molar ratio of the second doping element to lithium in the solid solution as (0.04~0.1):(1.4~1.5), for example, 0.04:1.5, 0.05:1.5, 0.06:1.5, 0.07:1.5, 0.08:1.5, 0.09:1.5, 1.0:1.5, 0.04:1.4, 0.05:1.4, 0.06:1.4, 0.07:1.4, 0.08:1.4, 0.09:1.4, 1.0:1.4.

[0024] When the first dopant Zr and the second dopant Hf are added simultaneously, the molar ratio of the first dopant Zr and the second dopant Hf is (3:2) to (2:3), for example, 3:2, 1:1, 2:3, preferably 1:1.

[0025] According to any embodiment of the first aspect of the present invention, in step S1, the sintering temperature is 800~1000℃ and the sintering time is 4~6h.

[0026] According to any embodiment of the first aspect of the present invention, in step S2, the calcination temperature is 800~1000℃ and the calcination time is 1~2h.

[0027] According to any embodiment of the first aspect of the present invention, the coating layer comprises, by mass ratio (30~40):(0.1~0.3):(1~6.0):(0.01~0.12):(1~3) a solid electrolyte material, a dispersant, a binder, a wetting agent and an additive.

[0028] According to any embodiment of the first aspect of the present invention, the diaphragm preferably comprises, by mass ratio (32-34):(0.25-0.3):(5.5-6.0):(0.1-0.12):(2.5-2.8) a solid electrolyte material, a dispersant, a binder, a wetting agent and an additive.

[0029] According to any embodiment of the first aspect of the invention, the dispersant comprises at least one selected from polyvinylpyrrolidone, polyacrylamide, lithium polyacrylate, sodium polyacrylate, and ammonium polyacrylate.

[0030] According to any embodiment of the first aspect of the invention, the adhesive comprises at least one selected from polyvinylidene fluoride, polyvinylidene fluoride-difluoropropylene, polyacrylic acid, polyacrylate, polyvinyl alcohol, and polyacrylamide.

[0031] According to any embodiment of the first aspect of the present invention, the wetting agent of the diaphragm includes at least one of polyacrylate, polyether-modified silane surfactant, and fatty alcohol polyether wetting agent, preferably, it can be polyether-modified polysiloxane.

[0032] According to any embodiment of the first aspect of the present invention, the diaphragm, the additives include at least one selected from sodium hydroxymethyl cellulose, styrene-butadiene, methylcellulose, carboxyethyl cellulose, and sodium alginate.

[0033] According to any embodiment of the first aspect of the invention, the total thickness of the coating layer of the diaphragm is 2~8 μm.

[0034] According to any embodiment of the first aspect of the present invention, the base membrane has a thickness of 7.0±1.0μm, a porosity of 40%~42%, and an air permeability of 150~180 sec / 100ml.

[0035] According to any embodiment of the first aspect of the present invention, the base membrane is made of polyethylene, polypropylene, or a copolymer of polyethylene and polypropylene.

[0036] According to any embodiment of the first aspect of the present invention, the diaphragm satisfies: Under conditions of 130℃ / 1h, the heat shrinkage rate MD≤2, for example, 2, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8; the heat shrinkage rate TD≤3, for example, 3, 2.9, 2.8, 2.7, 2.6, 2.5, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, 1.8, 1.7, 1.6, 1.5; Ionic conductivity ≥1.70 mS / cm, for example, 1.70 mS / cm, 1.71 mS / cm, 1.72 mS / cm, 1.75 mS / cm, 1.8 mS / cm, 1.85 mS / cm, 1.9 mS / cm, 1.95 mS / cm, 1.98 mS / cm, 2.0 mS / cm, 2.03 mS / cm, 2.05 mS / cm, 2.08 mS / cm, 2.10 mS / cm, 2.15 mS / cm, 2.2 mS / cm, 2.25 mS / cm, 2.3 mS / cm, 2.35 mS / cm, 2.36 mS / cm; Puncture strength ≥490 gf, for example, 490 gf, 495 gf, 497 gf, 500 gf, 502 gf, 504 gf, 505 gf, 510 gf, 511 gf, 512 gf, 515 gf, 516 gf, 519 gf, 520 gf, 525 gf, 527 gf, 530 gf, 532 gf; Breathability is 170~200 sec / 100cc, for example, 170 sec / 100cc, 173 sec / 100cc, 175 sec / 100cc, 176 sec / 100cc, 177 sec / 100cc, 179 sec / 100cc, 180 sec / 100cc, 181 sec / 100cc, 185 sec / 100cc, 186 sec / 100cc, 188 sec / 100cc, 189 sec / 100cc, 190 sec / 100cc, 192 sec / 100cc, 195 sec / 100cc, 197 sec / 100cc, 200 sec / 100cc; Porosity is 42%~48%, for example, 42%, 42.1%, 42.16%, 42.2%, 42.3%, 42.38%, 42.4%, 42.5%, 42.6%, 42.7%, 42.75%, 42.8%, 42.9%, 42.93%, 43%, 43.1%, 43.2%, 43.26%, 43.3%, 43.4%, 43.5%, 43.6%, 43.67%, 43.7%, 43.8%, 43.9%, 44%, 44.1%, 44.19%, 44.2%, 44.27%, 44.3%, 44.4%, 44.5%, 4 4.6%, 44.7%, 44.8%, 44.84%, 44.9%, 45%, 45.1%, 45.2%, 45.3%, 45.4%, 45.5%, 45.6%, 45.7%, 45.8%, 45.9%, 46%, 46.1%, 46.2%, 46.3%, 46.4%, 46.5%, 46.6%, 46.7%, 46.8%, 46.81%, 46.9%, 47%, 47.1%, 47.2%, 47.3%, 47.4%, 47.5%, 47.52%, 47.6%, 47.7%, 47.8%, 47.9%, 48%.

[0037] This membrane can stabilize the crystal lattice and suppress Ti. 4+ Reduced, possessing suitable porosity and permeability, it enhances ion conduction and blocks lithium dendrites, making it suitable for semi-solid-state lithium-ion batteries; it can effectively reduce interface impedance, solving the problems of poor solid-solid contact and high grain boundary impedance; and it suppresses Ti... 4+The reduction process enhances material stability, effectively improves the ionic conductivity of semi-solid batteries, and exhibits low thermal shrinkage and high puncture strength at 130℃.

[0038] A second aspect of this invention discloses a method for preparing a diaphragm, comprising the following raw materials: Coating slurry: The solid components include solid electrolyte materials, dispersants, binders, wetting agents, and additives in a mass ratio of (30~40):(0.1~0.3):(1.0~6.0):(0.01~0.12):(1-3), and the amount of liquid components added is 5~8 times the mass of the solid components; The steps include: applying the coating slurry onto the base film, controlling the coating temperature at 70±20℃ and the coating speed at 120±20m / min during the coating process.

[0039] According to any embodiment of the second aspect of the present invention, the preparation method of the diaphragm comprises, by mass ratio (32~34):(0.25~0.3):(5.5~6.0):(0.1~0.12):(2.5~2.8) a solid electrolyte material, a dispersant, a binder, a wetting agent, and an additive, and the amount of liquid component added is 6~7 times the mass of the solid component.

[0040] In the method for preparing the diaphragm according to any embodiment of the second aspect of the present invention, the liquid component is water.

[0041] According to any embodiment of the second aspect of the present invention, the method for preparing the diaphragm employs a roller coating process, which may be, for example, double-sided roller coating or single-sided roller coating.

[0042] The method for preparing a diaphragm according to any embodiment of the second aspect of the present invention further includes the step of: placing the coated diaphragm in an environment with a humidity of less than 1% for 4-6 hours to further improve structural stability and mechanical strength. This step can slowly remove residual moisture from the coating layer, promote cross-linking and curing of the adhesive, enhance the bonding strength between the coating layer and the base membrane, optimize the pore structure of the coating layer, prevent the coating layer from cracking and powdering, protect the coating layer from moisture damage, ensure high ionic conductivity, and at the same time reduce the high-temperature thermal shrinkage rate of the diaphragm, thereby improving the mechanical and thermal safety performance of the diaphragm.

[0043] The treated separator was subjected to performance tests, including the thermal shrinkage rate of the separator after baking at 130℃ for 1 hour and the ionic conductivity of the separator sample with a diameter of φ20mm assembled into a button cell.

[0044] The limiting factors for the "ionic conductivity" mentioned here are: lattice mismatch when LATP and LAGP are physically mixed only, resulting in a space charge layer that hinders lithium-ion transport, leading to high impedance; and the Ti in LATP... 4+The lattice of electrolytes is easily destroyed by lithium metal reduction, blocking lithium-ion transport channels; the small contact area between electrolyte particles results in high resistance to lithium-ion migration. This application addresses this by high-temperature sintering of LATP and LAGP in a specific ratio to form a solid solution, which eliminates the two-phase interface and constructs a continuous lithium-ion conduction channel; further, Zr and / or Hf doping modification is introduced, with Zr... 4+ Expanding the lattice transport aperture enhances conductivity, Hf 4+ Stable lattice suppression Ti 4+ The reduction process, in turn, works synergistically to lower grain boundary impedance and effectively improve ionic conductivity.

[0045] The limiting factors for the "thermal shrinkage rate" mentioned here are: the base film is prone to shrinkage and deformation due to the relaxation of polymer chains caused by heating; insufficient adhesion of the coating layer and loose powder make the coating layer easy to fall off at high temperatures, pulling on the base film and increasing shrinkage; after the coating layer is prepared by gravure roller coating process, it is placed in an environment with a relative humidity of less than 1% for 4 to 6 hours for low-temperature curing. The low humidity environment slowly removes the moisture inside the coating layer, promotes the cross-linking and curing of various binders, and the rigid coating layer is tightly attached to the surface of the base film. The polymer chains of the base film are bound to creep under heat, reducing the thermal shrinkage rate of the diaphragm at high and low temperatures. In this way, the problem of poor physical contact between solid and solid interfaces between solid electrolytes is solved. The electrode material expands and contracts drastically during charging and discharging, which makes it easy to separate from the rigid solid electrolyte membrane, creating gaps and causing contact failure.

[0046] The limiting factors for the "strength" mentioned here are: the solid electrolyte powder itself has large interparticle gaps and numerous pores, resulting in loose adhesion of the coating layer, easy powder shedding, and cracking; the single electrolyte crystal skeleton has low strength and is difficult to withstand the puncture stress of lithium dendrites. This application uses a Zr and / or Hf doped modified solid solution combined with a binder to form a slurry for coating, followed by low-humidity curing. 4+ Hf 4+ Zr can optimize the density of crystals. 4+ It can accelerate atomic diffusion, promote grain growth, and expel pores; Hf 4+ By relying on strong chemical bonds to fix the grain boundaries, the grains are more firmly bonded. The combination of two ions can counteract the lattice expansion stress caused by individual doping, making it less prone to cracking and pore blockage during sintering. It also avoids the formation of insulating oxide impurities, keeps the grain boundary diffusion channels unobstructed, and ultimately produces a solid electrolyte material with higher density. The binder cross-links to form a base film coating composite network, and the rigid solid electrolyte material disperses external forces, significantly improving the tear and puncture resistance of the membrane coating.

[0047] The limiting factors for "air permeability" mentioned here are: poor slurry dispersion leading to powder agglomeration and blockage of micropores; excessively fast drying rate easily forming a dense skin layer on the coating surface; and excessive addition of binder blocking the original pores of the diaphragm. This application achieves good slurry dispersion by limiting the proportions of each component in the slurry, uniform gravure coating combined with slow moisture-controlled drying, and avoiding particle agglomeration and pore blockage through reasonable proportions. Low-temperature and slow film formation ensures that the coating layer retains the interconnected microporous structure, thus maintaining the stable air permeability of the diaphragm while ensuring the coating layer is firm.

[0048] The limiting factors for "porosity" mentioned here are: rapid high-temperature drying causes moisture to escape instantly, resulting in pore collapse and blockage; an imbalance in the doping ratio easily leads to abnormal grain growth and excessive densification of the coating layer, resulting in a significant reduction in porosity. This application addresses this by limiting the ratio of LATP and LAGP and optimizing Zr... 4+ / Hf 4+ The doping amount, combined with slow dehydration and curing under low humidity, allows for appropriate doping to control the grain size and avoid excessive grain density that would reduce ionic conductivity. Slow dehydration and molding ensure uniform distribution of micropores, balancing the adhesion of the coating layer with suitable porosity, which facilitates electrolyte wetting of the storage solution.

[0049] The limiting factor for "structural stability" mentioned here is: in a pure LATP system, Ti 4+ Lithium reduction easily disrupts the regularly arranged crystal framework; simultaneously, the inconsistent thermal expansion coefficients of LATP and LAGP lead to uneven interfacial stress and delamination cracking when simply mixed. This application addresses this by high-temperature sintering of LATP and LAGP into a solid solution, followed by co-doping with Zr and / or Hf to generate a solid solution that unifies the thermal expansion coefficients of the two phases and eliminates interfacial thermal stress; Hf 4+ Zr relies on high bond energy to anchor the lattice framework 4+ Optimize the stress distribution within the lattice to synergistically suppress Ti 4+ The coating is regenerated and does not easily powder or peel off during charge-discharge cycles, thus maintaining the overall structural stability of the diaphragm for a long time.

[0050] Test method: Methods for testing ionic conductivity: The test was conducted according to the method specified in NB / T10827-2021. A φ20mm sample (φ20mm represents the diameter of a circular sample of 20mm) was cut and assembled with the positive and negative electrode shells of a CR2016 button cell to form a button cell. The electrolyte was LiPF6 1mol / L, EC:EMC = 3:7, and VC = 2.0wt%. The button cell was assembled in the following order: negative electrode shell, separator, gasket (φ15.8*0.5mm, i.e., the diameter of the gasket is 15.8mm and the thickness is 0.5mm), corrugated spring, and positive electrode shell. Four drops of electrolyte were added using a 1mL dropper to fully wet the separator. The battery was sealed with a sealing machine, and the electrolyte on the surface of the button cell was wiped clean with alcohol. The battery was then left to stand for 3 hours. The electrochemical workstation (Metrohm, PGSTAT204) was turned on, and the "Impedance Test" was selected for testing. The lower frequency limit was 10000Hz, the upper frequency limit was 100000Hz, and the current was 100mA. The resistance of batteries composed of one, two, three, and four separator layers was tested, with three sets of parallel data for each sample. A curve was plotted with the number of separator layers on the x-axis and the corresponding battery resistance on the y-axis. The slope of the curve with a goodness of fit ≥0.99 is the separator resistance R (Ω). The separator ionic conductivity is calculated as d / (R*A) (S / cm), where d is the separator thickness in cm and A is the effective area of ​​the gasket in cm². 2 . Test method for heat shrinkage rate: The test was conducted according to the requirements of GB / T36363-2018. A 10cm × 10cm sample was cut, and the transverse (TD) and longitudinal (MD) widths were marked on the sample. The transverse and longitudinal widths were measured using a fully automatic image measuring projector (Kunshan Gaopin Precision Instrument Co., Ltd., GP-300C). The sample was held between two sealed A4 sheets of paper and placed in a 130℃ oven for 1 hour. After the sample returned to room temperature, the transverse and longitudinal widths were measured again using the fully automatic image measuring projector. The measurement was repeated three times, and the average value was taken.

[0051]

[0052]

[0053] Methods for testing puncture strength: Cut a diaphragm with a size of 50*100 mm along the TD direction. Fix the diaphragm on the sample holder of the puncture test machine (model: KES-GNDG5, KNC Technology Co., Ltd.). Use a steel needle with a diameter of 1.0 mm to puncture the diaphragm at a speed of 0.1 cm / sec. Read the maximum load of the steel needle penetrating the diaphragm. Perform the test more than 5 times and take the arithmetic mean.

[0054] Methods for testing air permeability: The test was conducted according to the requirements of JIS P 8117-2009 "Paper and paperboard - Determination of air permeability and air resistance (medium range) - Gourle method". A 600mm × 100mm battery separator sample with a coating was cut and measured using a Wangyan-type air permeability meter (ASAHI Corporation, EG01-55-1MR). The test time was 3s. The air permeability of the separator was measured at arbitrary positions at 100mm intervals along the 600mm TD direction. The average value of the above 5 test points was recorded as the air permeability of the separator.

[0055] Porosity testing methods: Base membrane and coated diaphragm samples were cut separately, with a sample size of 10cm × 10cm. The thickness H of the two samples was measured using a Mahr thickness gauge (Mahr, C1202). B (Base membrane), H1 (diaphragm with coating), H1-H B The coating thickness ΔH is obtained.

[0056] The mass M of the two samples was measured using an electronic balance (Mettler-Toledo Instruments (Shanghai) Co., Ltd., ME204E / 02). B (Base membrane), M1 (diaphragm with coating), M1-M B The weight ΔM of the coating layer (in g) is obtained.

[0057] Calculate the surface density (in g / cm³) using the formula D = M / (L × B). 2 In this equation, M represents the mass of the sample (in grams), L represents the length of the sample (in centimeters), and B represents the width of the sample (in centimeters). The density of the coating layer is calculated as ΔD = ΔM / (L × B). The true density ρ of the coating layer is found to be 0.95 g / cm³. 3 The porosity (in %) of the coating layer is obtained by p = (1 - ΔD / ΔH / ρ) × 100%.

[0058] Methods for testing average particle size: If the raw material is known, the particle size of the inorganic particles is determined according to the national standard GB / T19077-2016 "Particle Size Distribution by Laser Method". Specifically, a laser particle size analyzer (Dandong Baite, BT-2600E) is used, and the dry method is selected for testing. The particles to be tested are fully ultrasonically dispersed and approximately 3 grams of the sample are added to the storage funnel. The feed is then started, and the pressure is set to approximately 0.2 MPa. The shading rate is controlled between 8-15%. Three sets of tests are performed, and the average value is obtained. 50 It refers to the particle size that, in the volumetric particle size distribution of a material, starts from the smallest particle size and reaches 50% of the cumulative volume.

[0059] A third aspect of the present invention provides a battery comprising: The diaphragm as described in any of the first aspects of the present invention; The diaphragm is prepared by the preparation method described in any of the second aspects of the present invention.

[0060] 3. Beneficial effects Compared with the prior art, the beneficial effects of the present invention are as follows: Addressing the technical issues: In semi-solid systems, ions must transport between solid electrolyte particles and between the solid electrolyte and electrode active particles. Solid-solid contact is a rigid point-to-point contact with a small effective contact area. Furthermore, a high-resistivity "interface barrier layer" is easily formed at the interface due to lattice mismatch, impurities, etc., resulting in the macroscopic apparent ionic conductivity of the semi-solid battery being far lower than the intrinsic value of the electrolyte material itself. (1) This invention introduces a solid electrolyte forming a solid solution phase into the membrane, where Zr and / or Hf are uniformly dissolved within the LATP / LAGP lattice. This optimizes lithium-ion conduction efficiency and improves conductivity, while also stabilizing Ti in the crystal structure. 4+ It improves the stability of the negative electrode interface, increases the effective contact area, reduces lattice mismatch and impurities, and effectively improves ionic conductivity; no significant volume expansion or contraction occurs during charging and discharging, and the membrane strength is effectively enhanced. (2) The present invention achieves good dispersion by limiting the proportion of each component of the slurry, uniformly coating with gravure and slow humidity control drying, and reasonable proportioning to avoid particle agglomeration and pore blockage. Low temperature and slow film formation ensure that the coating layer retains the through-pore structure, and maintains the stable air permeability of the diaphragm on the premise of ensuring the coating layer is firm. Attached Figure Description

[0061] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. However, it should be understood that these drawings are designed for illustrative purposes only and are not intended to limit the scope of the present invention. Furthermore, unless specifically indicated, these drawings are intended only to conceptually illustrate the structural construction described herein and are not necessarily drawn to scale.

[0062] Figure 1 This is a schematic diagram of a semi-solid lithium-ion battery separator. Detailed Implementation

[0063] The following detailed description of exemplary embodiments of the invention is taken with reference to the accompanying drawings, which form part of the description and illustrate exemplary embodiments in which the invention may be practiced. While these exemplary embodiments have been described in sufficient detail to enable those skilled in the art to practice the invention, it should be understood that other embodiments may be implemented and various changes may be made to the invention without departing from the spirit and scope thereof. The more detailed description of embodiments of the invention below is not intended to limit the scope of the claimed invention, but is merely illustrative and not restrictive of the description of the features and characteristics of the invention, to suggest the best mode for carrying out the invention, and is sufficient to enable those skilled in the art to practice the invention. Therefore, the scope of the invention is defined only by the appended claims.

[0064] Example 1 (1) Solid electrolyte materials: The solid electrolyte material is coated on one or both sides of the base film, and the coating layer includes the solid electrolyte material, which is Li. 1.5 Al 0.5 Zr 0.05 Hf 0.05 Ti 1.12 Ge 0.28 (PO4)3, particle size D of solid electrolyte material 50 It is 0.896 μm.

[0065] (2) A method for preparing solid electrolyte materials, including the following steps: S1, 80 kg of LATP and 20 kg of LAGP are mixed and sintered in air to form a solid solution. The sintering temperature is 800 ± 50 °C and the sintering time is 5 h. S2. Grind 1.5 kg of zirconium oxynitrate ZrO(NO3)2·2H2O and 3.0 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material. The calcination temperature is 800℃ and the calcination time is 1.5 h.

[0066] The mass ratio of LATP to LAGP is 4:1.

[0067] (3) A diaphragm, including: Base membrane; polyethylene diaphragm, 7 μm thick, porosity 40%~42%, air permeability 150~180 sec / 100ml; Coating layer: Coated on both sides of the base film, with a thickness of 2 μm on each side. The coating layer includes a solid electrolyte material of Li. 1.5 Al 0.5 Zr 0.05 Hf 0.05 Ti 1.12Ge 0.28 (PO4)3; (4) The preparation method of the diaphragm, including raw materials: The solid components of the coating slurry include 33 kg of solid electrolyte material, 0.275 kg of sodium polyacrylate dispersant, 5.75 kg of polyacrylate binder, 0.11 kg of polyether-modified polysiloxane wetting agent, 2.65 kg of sodium carboxymethyl cellulose additive, and 59.5 kg of water as the liquid component.

[0068] Including the following steps: The solid electrolyte material, Li, was generated using a solid-state calcination method. 1.5 Al 0.5 Zr 0.05 Hf 0.05 Ti 1.12 Ge 0.28 (PO4)3; The coating slurry is applied to the base film using a gravure roller coating process. During the coating process, the coating temperature is controlled at 70℃ and the coating speed is 120m / min.

[0069] Place the coated diaphragm in an environment with ≤1% humidity for 4 hours.

[0070] (5) A battery, comprising: Solid electrolyte materials as described in (1); Solid electrolyte materials prepared by the preparation method described in (2); The diaphragm as described in (3); The diaphragm is prepared by the method described in (4).

[0071] Example 2 This embodiment is basically the same as Embodiment 1, except that the doping amounts of Zr and Hf are changed. (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.06 Hf 0.04 Ti 1.12 Ge 0.28 (PO4)3, particle size D of solid electrolyte material 50 It is 1.134 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 80 kg of LATP and 20 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 1.8 kg of ZrO(NO3)2·2H2O and 2.4 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0072] Example 3 This embodiment is basically the same as Embodiment 1, except that the doping amounts of Zr and Hf are changed. (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.04 Hf 0.06 Ti 1.12 Ge 0.28 (PO4)3, particle size D of solid electrolyte material 50 It is 0.803 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 80 kg of LATP and 20 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 1.2 kg of ZrO(NO3)2·2H2O and 3.6 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0073] Example 4 This embodiment is basically the same as Embodiment 1, except that it is not doped with Zr; (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Hf 0.1 Ti 1.12 Ge 0.28 (PO4)3, particle size D of solid electrolyte material 50 It is 0.762 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 80 kg of LATP and 20 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 6.0 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0074] Example 5 This embodiment is basically the same as Embodiment 1, except that it is not doped with Hf; (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.1 Ti1.12 Ge 0.28 (PO4)3, particle size D of solid electrolyte material 50 It is 1.346 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 80 kg of LATP and 20 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 3.0 kg of ZrO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0075] Example 6 This embodiment is basically the same as Example 1, except that the mass ratio of LATP to LAGP is changed to 1:4. (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.05 Hf 0.05 Ti 0.28 Ge 1.12 (PO4)3, particle size D of solid electrolyte material 50 It is 1.149 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 20 kg of LATP and 80 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 1.5 kg of zirconium oxynitrate ZrO(NO3)2·2H2O and 3.0 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0076] Example 7 This embodiment is basically the same as Example 1, except that the mass ratio of LATP to LAGP is changed to 1:1. (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.05 Hf 0.05 Ti 0.7 Ge 0.7 (PO4)3, particle size D of solid electrolyte material 50 It is 1.107 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 50 kg of LATP and 50 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 1.5 kg of zirconium oxynitrate ZrO(NO3)2·2H2O and 3.0 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0077] Example 8 This embodiment is basically the same as Example 1, except that the mass ratio of LATP to LAGP is changed to 3:2. (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.05 Hf 0.05 Ti 0.84 Ge 0.56 (PO4)3, particle size D of solid electrolyte material 50 It is 1.107 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 60 kg of LATP and 40 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 1.5 kg of zirconium oxynitrate ZrO(NO3)2·2H2O and 3.0 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0078] Example 9 This embodiment is basically the same as embodiment 1, except that the weight of water in the slurry is increased; Coating slurry: The solid components, by mass ratio, include 33 kg of solid electrolyte material, 0.275 kg of dispersant acrylic polymer, 5.75 kg of binder polyacrylate, 0.11 kg of wetting agent polyether-modified polysiloxane, 2.65 kg of auxiliary agent sodium carboxymethyl cellulose, and 79.5 kg of liquid component water.

[0079] Example 10 This embodiment is basically the same as Embodiment 1, except that the coated diaphragm was not placed in a humid environment.

[0080] Example 11 This embodiment is basically the same as Embodiment 1, except that the sintering temperature in step S1 is 1000℃, and the particle size D of the solid electrolyte material is... 50 It is 1.213 μm.

[0081] Example 12 This embodiment is basically the same as Embodiment 1, except that the calcination temperature in step S2 is 1000℃, and the particle size D of the solid electrolyte material is... 50 It is 1.304 μm.

[0082] Comparative Example 1 This comparative example is basically the same as Example 1, except that it is not doped with Zr and Hf. (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Ti 1.2 Ge 0.3 (PO4)3, particle size D of solid electrolyte material 50 It is 0.803 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 80 kg of LATP and 20 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind the solid solution evenly and then calcine it.

[0083] Comparative Example 2 This comparative example is basically the same as Example 1, except that LATP was not added; (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.05 Hf 0.05 Ge 1.4 (PO4)3, particle size D of solid electrolyte material 50 It is 1.273 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 100 kg of LAGP, is sintered in air to form a solid solution; S2. Grind 1.5 kg of zirconium oxynitrate ZrO(NO3)2·2H2O and 3.0 kg of HfO(NO3)2·2H2O with LAGP solid solution until homogeneous, and then calcine to form a metal-doped material.

[0084] Comparative Example 3 This comparative example is basically the same as Example 1, except that LAGP was not added; (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.05 Hf 0.05 Ti 1.4 (PO4)3, particle size D of solid electrolyte material 50It is 0.853 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 100 kg of LATP, is sintered in air to form a solid solution; S2. Grind 1.5 kg of zirconium oxynitrate ZrO(NO3)2·2H2O and 3.0 kg of HfO(NO3)2·2H2O with LATP solid solution until homogeneous, and then calcine to form a metal-doped material.

[0085] Comparative Example 4 This comparative example is basically the same as Example 1, except that LATP and LAGP are only physically mixed and not sintered, and the particle size D of the solid electrolyte material is different. 50 It is 0.881 μm.

[0086] Comparative Example 5 This comparative example is basically the same as Example 4, except that LATP and LAGP are only physically mixed, and the particle size D of the solid electrolyte material is different. 50 It is 0.784 μm.

[0087] Comparative Example 6 This comparative example is basically the same as Example 5, except that LATP and LAGP are only physically mixed, and the particle size D of the solid electrolyte material is different. 50 It is 1.357 μm.

[0088] Comparative Example 7 This comparative example is basically the same as Example 1, except that the amount of Zr doping is too high compared to Example 1. (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.15 Hf 0.05 Ti 1.04 Ge 0.26 (PO4)3, particle size D of solid electrolyte material 50 It is 0.915 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 80 kg of LATP and 20 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 4.5 kg of zirconium oxynitrate ZrO(NO3)2·2H2O and 3.0 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0089] Comparative Example 8 This comparative example is basically the same as Example 1, except that the amount of Zr doping is too small. (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.01 Hf 0.05 Ti 1.15 Ge 0.29 (PO4)3, particle size D of solid electrolyte material 50 It is 0.793 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 80 kg of LATP and 20 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 0.3 kg of zirconium oxynitrate ZrO(NO3)2·2H2O and 3.0 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0090] Comparative Example 9 This comparative example is basically the same as Example 1, except that the amount of Hf doping is too high. (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.05 Hf 0.15 Ti 1.04 Ge 0.26 (PO4)3, particle size D of solid electrolyte material 50 It is 0.952 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 80 kg of LATP and 20 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 1.5 kg of zirconium oxynitrate ZrO(NO3)2·2H2O and 9.0 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0091] Comparative Example 10 This comparative example is basically the same as Example 1, except that the amount of Hf doping is too small. (1) Solid electrolyte material: The solid electrolyte material Li 1.5 Al 0.5 Zr 0.05 Hf 0.01 Ti 1.15 Ge 0.29 (PO4)3, particle size D of solid electrolyte material50 It is 0.917 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 80 kg of LATP and 20 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 1.5 kg of zirconium oxynitrate ZrO(NO3)2·2H2O and 1.0 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0092] Comparative Example 11 This comparative example is basically the same as Example 1, except that the doping amount of Zr is much greater than that of Hf. (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.1 Hf 0.01 Ti 1.12 Ge 0.28 (PO4)3, particle size D of solid electrolyte material 50 It is 0.788 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 80 kg of LATP and 20 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 3.0 kg of zirconium oxynitrate ZrO(NO3)2·2H2O and 0.6 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0093] Comparative Example 12 This comparative example is basically the same as Example 1, except that the doping amount of Zr is much smaller than that of Hf. (1) Solid electrolyte material: The solid electrolyte material is Li 1.5 Al 0.5 Zr 0.01 Hf 0.1 Ti 1.12 Ge 0.28 (PO4)3, particle size D of solid electrolyte material 50 It is 0.774 μm; (2) A method for preparing solid electrolyte materials, including the following steps: S1, 80 kg of LATP and 20 kg of LAGP are mixed and sintered in air to form a solid solution; S2. Grind 0.3 kg of zirconium oxynitrate ZrO(NO3)2·2H2O and 6.0 kg of HfO(NO3)2·2H2O with the solid solution until homogeneous, and then calcine to form a metal-doped material.

[0094] Table 1. Diaphragm performance of the examples and comparative examples

[0095] This application uses Zr. 4+ / Hf 4+ Single-doped or co-doped LATP / LAGP composites form highly conductive solid solutions, significantly improving ionic conductivity. LAGP is used to optimize grain boundary transport, reduce interfacial impedance, and address issues of poor solid-solid contact and high grain boundary impedance; doping can suppress Ti... 4+ The process reduces material stability. Through gravure roller coating and low-humidity strengthening treatment, the separator's thermal shrinkage rate at 130℃ is only 1%~2%, significantly improving its mechanical and thermal safety performance. This solution balances high ion conductivity, high stability, and mass production feasibility, comprehensively improving the interface and rate performance of semi-solid-state batteries, while combining the maturity of liquid-state processes with the safety of solid-state batteries. The final separator exhibits an ionic conductivity ≥1.70 mS / cm, preferably ≥2 mS / cm, and more preferably ≥2.3 mS / cm.

[0096] The above description is merely a preferred embodiment of this application and an explanation of the technical principles used. Those skilled in the art should understand that the scope involved in this application is not limited to the technical solutions formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept. For example, technical solutions formed by replacing the above-mentioned features with technical features with similar functions disclosed in this application (but not limited to) each other.

[0097] Apart from the technical features described in the specification, the other technical features are known to those skilled in the art. To highlight the innovative features of this invention, the other technical features will not be described in detail here.

Claims

1. A diaphragm, including: Base membrane: Polyolefin separator; Coating layer: coated on one or both sides of the base film, the coating layer comprising a solid electrolyte material; Its features are, The solid electrolyte material is a solid solution formed by LATP and LAGP, and is prepared by Hf and / or Zr doping, wherein the mass ratio of LATP to LAGP is (4:1) to (1:4).

2. The diaphragm according to claim 1, characterized in that, The average particle size D of solid electrolyte materials 50 The thickness ranges from 0.70 μm to 1.4 μm. The solid electrolyte material is Li a Al b M1 x M2 y M3 m M4 n (PO4) c , Where M1 is Zr, M2 is Hf, M3 is Ti, M4 is Ge, a=1.4~1.5, b=0.4~0.6, c=3, x=0~0.1, y=0~0.1, m=0.1~1.5, n=0.1~1.5, and x and y are not both 0.

3. The diaphragm according to claim 1, characterized in that, The preparation method of the solid electrolyte material includes the following steps: S1. Mix LATP and LAGP and sinter in air to form a solid solution; S2. The dopant source is coated on the surface of the solid solution and then calcined to form a metal-doped solid electrolyte material.

4. The diaphragm according to claim 3, characterized in that, In step S1, the sintering temperature is 800~1000℃ and the sintering time is 4-6h; In step S2, the calcination temperature is 800~1000℃ and the calcination time is 1~2h.

5. The diaphragm according to claim 3, characterized in that, In step S2, the doping source includes a first doping source and / or a second doping source. The first doping source is used to provide the first doping element Zr, which is selected from at least one of ZrO(NO3)2·2H2O, Zr(NO3)4, ZrOCl2·8H2O, ZrO2, and Zr(CO3)2. The amount of the first doping element added satisfies the molar ratio of the first doping element to lithium in the solid solution as (0.04~0.1):(1.4~1.5). The second doping source is used to provide the second doping element Hf. The second doping source is selected from at least one of HfO(NO3)2·2H2O, HfCl4, HfO2, and Hf(OH)4. The amount of the second doping element added satisfies that the molar ratio of the second doping element to the lithium element in the solid solution is (0.04~0.1):(1.4~1.5).

6. The diaphragm according to claim 1, characterized in that, The coating layer comprises, by mass ratio (30~40):(0.1~0.3):(1~6.0):(0.01~0.12):(1~3) a solid electrolyte material, dispersant, binder, wetting agent and additives; The dispersant includes at least one of polyvinylpyrrolidone, polyacrylamide, lithium polyacrylate, sodium polyacrylate, and ammonium polyacrylate; The adhesive includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-difluoropropylene, polyacrylic acid, polyacrylate, polyvinyl alcohol, and polyacrylamide; The wetting agent includes at least one of polyacrylate, polyether-modified silane surfactant, and fatty alcohol polyether wetting agent; The additives include at least one of sodium hydroxymethyl cellulose, styrene-butadiene, methylcellulose, carboxyethyl cellulose, and sodium alginate.

7. The diaphragm according to any one of claims 1-6, characterized in that, The diaphragm satisfies: Under the condition of 130℃ / 1h, the heat shrinkage rate MD≤2 and the heat shrinkage rate TD≤3; Ionic conductivity ≥1.70 mS / cm; Puncture strength ≥490 gf; Breathability is 170~200 sec / 100cc.

8. The method for preparing the diaphragm according to any one of claims 1-7, characterized in that, Raw materials include: LATP, LAGP, ZrO(NO3)2·2H2O, and HfO(NO3)2·2H2O; Coating slurry: The solid components include solid electrolyte materials, dispersants, binders, wetting agents and additives in the mass ratio of (30~40):(0.1~0.3):(1~6.0):(0.01~0.12):(1~3); The steps include: applying the coating slurry onto the base film, controlling the coating temperature at 70±20℃ and the coating speed at 120±20m / min during the coating process; The coating method employs a roller coating process.

9. The method for preparing the diaphragm according to claim 8, characterized in that, It also includes the step of placing the coated diaphragm in an environment with less than 1% humidity for 4-6 hours.

10. A battery, characterized in that, include: The diaphragm as described in any one of claims 1-7; The diaphragm prepared by the method according to any one of claims 8-9.